2008
DOI: 10.1038/ejhg.2008.129
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetics of hereditary non-syndromic colorectal cancer

Abstract: Previously we have localized to chromosome 3q21-q24, a predisposition locus for colorectal cancer (CRC), through a genome-wide linkage screen (GWLS) of 69 families without familial adenomatous polyposis or hereditary non-polyposis CRC. To further investigate Mendelian susceptibility to CRC, we extended our screen to include a further GWLS of an additional 34 CRC families. We also searched for a disease gene at 3q21-q24 by linkage disequilibrium mapping in 620 familial CRC cases and 960 controls by genotyping 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Several chromosomal regions have been linked to CRC susceptibility, including 3q21-q24, 7q31, 9q22.2-31.2, 11q23.2, 11q13.4, 14q24.2 and 22q12.1. [8][9][10][11][12][13] However, none of these studies have led to the identification of a novel CRC susceptibility gene yet.…”
mentioning
confidence: 99%
“…Several chromosomal regions have been linked to CRC susceptibility, including 3q21-q24, 7q31, 9q22.2-31.2, 11q23.2, 11q13.4, 14q24.2 and 22q12.1. [8][9][10][11][12][13] However, none of these studies have led to the identification of a novel CRC susceptibility gene yet.…”
mentioning
confidence: 99%
“…Similar to ours, these studies [7][8][9][10][11][12][13][14][15] used similar sample size and also excluded families with mutations in known predisposition genes for CRC to maximise the likelihood of discovering novel CRC risk genes. However, their experimental designs showed differences with each other and with ours.…”
Section: Iw Saunders Et Almentioning
confidence: 69%
“…These included the degree to which families were stratified by clinical phenotypes, 9 whether unaffected relatives were included or excluded from the linkage analyses and whether subjects with AA but no adenocarcinoma were classified as affected. [7][8][9][10][11][12][13][14][15] A feature of all these studies, including ours, is that while promising candidate regions have been identified, there is limited concordance in the regions identified. Independent confirmation of common regions between studies has only been achieved for regions on 3q 7,10,12 and 9q22.…”
Section: Iw Saunders Et Almentioning
confidence: 99%
See 2 more Smart Citations